Preparation method of Janus water-based microgel

The preparation of Janus water-based microgels by one-step vortex method solves the problems of expensive equipment and slow preparation speed in the prior art, and achieves efficient and low-cost industrial production, and has adjustable particle size.

CN119409879AActive Publication Date: 2025-02-11YANGZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411787215.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing preparation methods of Janus water-based microgels have problems such as expensive equipment, slow preparation speed, and difficult to achieve industrial production.

Method used

Janus emulsion was prepared by a one-step vortex method by emulsifying the two-aqueous phase system of polymerized monomers and an oil solution of surfactant in one-time. The three-dimensional network structure was formed by ultraviolet photopolymerization to obtain Janus water-based microgel.

Benefits of technology

It realizes simple and efficient preparation of Janus water-based microgels, reduces production costs, increases yield, and has adjustable particle size, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409879A_ABST
    Figure CN119409879A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of Janus water-based microgel, and belongs to the technical field of microgel. According to the preparation method, the Janus water-based microgel is successfully prepared by taking vortex oscillation emulsion formation as a basis and taking ultraviolet irradiation as a polymerization mode. The method comprises the following steps: 1, preparing a solution: weighing a polymeric monomer / a cross-linking agent / an initiator, and preparing an oil phase solution containing a Span 80 surfactant; preparing an ATPS aqueous solution; 2, preparation of liquid drops of the Janus emulsion; 3, preparation of the Janus water-based microgel; and 4, washing the Janus water-based microgel. The oil phase and the surfactant used in the invention are cheap and easily available, the preparation method is simple, and Janus water-based microgels with different morphologies can be obtained by changing the aqueous two-phase components and the types of the surfactant. The Janus water-based microgel prepared by the invention is expected to be used for drug encapsulation and treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a gel, and in particular to a method for preparing a Janus water-based microgel. Background Art

[0002] The main method for preparing Janus water-based microgels is microfluidics, which can achieve various topological changes of the gel, but the microfluidics equipment is expensive and the preparation speed is slow, making it difficult to achieve industrial preparation. Therefore, we developed a one-step vortex method to prepare Janus water-based microgels, which can prepare Janus emulsions in batches through a vortex, and use the Janus emulsions as templates to carry out polymerization reactions in them to prepare Janus microgels, thus achieving batch preparation of Janus water-based microgels.

[0003] At present, the polymerization methods of microgels mainly include photopolymerization, ionic crosslinking and thermal polymerization. Among them, ionic crosslinking is mainly used to prepare physical gels, using the interaction between ions and polymers to strengthen the gel network; thermal polymerization uses thermal initiators such as ammonium persulfate and sodium persulfate to initiate chain polymerization to form a three-dimensional network, but thermal polymerization is not an ideal polymerization method because it is difficult to ensure the stability of the reverse emulsion under high temperature environment. Photopolymerization uses photoinitiators to initiate chain polymerization, and because it is rapidly prepared, it is widely used in the preparation of microgels and solid particles.

[0004] For example, the invention patent in publication number CN103788267A discloses a method for preparing double-sided particles, wherein two incompletely miscible polymerizable monomers are emulsified with an aqueous surfactant solution to prepare a double-sided emulsion, and then the polymerizable monomers in the emulsion droplets are polymerized by photoinitiation to prepare double-sided particles composed of two different organic substances. For example, publication number CN115418006A discloses a microgel based on acryloylated gelatin, a preparation method and its application, and a high-throughput preparation of an acryloylated gelatin microgel using a microfluidic method combined with an online photopolymerization reaction, and its application in the encapsulation of bioactive substances. First, acryloylated gelatin microdroplets are prepared with high throughput using droplet microfluidics technology, and then a visible light source matched with a photoinitiator is placed above the microfluidic pipeline to achieve online continuous production of GelA microdroplets and solidify to form microgel particles.

[0005] At present, these methods need to be further improved in production process, production volume, and morphology control. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a simple, efficient and industrially-friendly method for preparing Janus water-based microgels.

[0007] Technical solution: A method for preparing Janus water-based microgel, comprising the following steps:

[0008] (1) Construction of a biphasic aqueous phase containing polymerized monomers: sodium sulfate and polyethylene glycol or dextran and polyethylene glycol (PEG) are added to deionized water, dissolved and centrifuged to form a biphasic aqueous ATPS solution, and polymerized monomers, crosslinking agents, and initiators are added to ATPS, stirred, dissolved, and centrifuged to obtain an ATPS aqueous solution with monomers added;

[0009] (2) Preparation of Janus emulsion and Janus microgel: prepare an oil solution containing a surfactant, add the ATPS aqueous solution containing the monomer to the oil solution containing the surfactant, use a vortex shaker to shake into an emulsion, place the emulsion in a light irradiation reaction chamber, and use ultraviolet light to irradiate and stir to obtain Janus microgel;

[0010] (3) Drying of Janus microgel: The Janus microgel obtained after light irradiation is washed and dried to obtain the Janus microgel.

[0011] In the preparation method, in step (1), the polymerization monomer is acrylamide, polyethylene glycol diacrylate or N-isopropyl acrylamide; the crosslinking agent is N,N′-methylenebisacrylamide; and the initiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone.

[0012] In the preparation method, the surfactant in step (2) is Span 80; the oil phase is liquid paraffin and sunflower oil; the emulsification speed of the emulsification using a vortex shaker is 2000-20000 rpm, and the emulsification time is 1-5 minutes.

[0013] In the method, if a rotor is used as an agitator in step (1), the rotation speed is 500 to 1000 rpm.

[0014] In the preparation method, the wavelength of the ultraviolet lamp in step (3) is 300-400nm.

[0015] In the preparation method, the washing in step (3) is to use ethanol and petroleum ether to wash and dry alternately to obtain the Janus water-based microgel.

[0016] In the preparation method, in step (1), the mass concentration of the polymerized monomer is 5% to 30%, the mass fraction of the initiator to the monomer is 0.1% to 3%, and the mass concentration of the crosslinking agent to the monomer is 1% to 20%.

[0017] In the preparation method, in step (2), the mass ratio of oil to water is 10 / 1 to 2 / 1, and the concentration of surfactant Span 80 in the oil is 1% to 5%.

[0018] In the preparation method, the mass concentration of PEG 8000 in step (1) is 10% to 25%, the mass concentration of DEX 10000 is 10% to 25%, and the mass concentration of sodium sulfate is 10% to 25%.

[0019] In the preparation method, the molecular weight of PEG is selected from 2000 to 25000, and the molecular weight of DEX is selected from 2000 to 25000.

[0020] This patent uses a one-step vortex method to emulsify a two-phase aqueous system with a polymerized monomer and an oil solution with a surfactant to prepare a Janus emulsion, and then polymerizes the Janus emulsion to form a three-dimensional network structure by ultraviolet polymerization, thereby obtaining a Janus water-based microgel, the morphology of which can be controlled by changing the ratio of the two-phase aqueous system, and the particle size can be controlled by the rotation speed of the vortex. The patent of this invention has the advantages of low production cost, high output, and adjustable microgel size.

[0021] The polymerizable monomers of the present invention include but are not limited to acrylamide, N-isopropylacrylamide, and polyethylene glycol diacrylate. These three monomers are common materials for preparing hydrogels and are cheap and readily available.

[0022] The initiator described in the present invention includes but is not limited to 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, which is a common cleavage-type photoinitiator with a simple structure, easy synthesis and high initiation activity.

[0023] The cross-linking agent of the present invention includes but is not limited to N,N'-methylenebisacrylamide.

[0024] The preparation process of Janus water-based microgels can be found in Figure 1 .

[0025] The present invention also confirms the Janus water-based microgel prepared by the present invention through an optical microscope, confirms the particle size of the prepared Janus water-based microgel through a laser particle size analyzer, confirms the morphology of the Janus water-based microgel prepared by the present invention through a scanning electron tunneling microscope (SEM), characterizes the microgel group after drying through an infrared spectrometer, and performs rheological property test on the prepared microgel through a rotational rheometer.

[0026] The preparation premise of Janus water-based microgel is Janus emulsion, and Janus emulsion depends on the preparation of two aqueous phases. When two polymers, a polymer and a lyophilic salt, or two salts (one is a discrete salt and the other is a lyophilic salt) are mixed together at an appropriate concentration or at a specific temperature, a two-phase aqueous system is formed. In most cases, these two phases are composed of water and non-volatile components, thus avoiding the use of volatile organic components. The molecules of the two substances in the two aqueous phases compete with each other for water molecules to form a phase interface. The two molecules have different abilities to compete for water molecules and different hydrophilicities, resulting in different positions of the phase interface. The two-phase aqueous system described in the present invention includes a salt solution and a polymer solution, a polymer and a polymer solution, the salt solution and the polymer solution are sodium sulfate and PEG 8000, and the polymer and the polymer are DEX 10000 and PEG 8000.

[0027] Beneficial effects: (1) Janus emulsion is used as a polymerization template to prepare Jansu microgel, and the obtained double-sided microgel has controllable morphology. The size of Janus water-based microgel can be controlled by the speed of vortexing, which is conducive to expanding the application field of Jansu. (2) The preparation method is simple, and the polymerization speed is fast using the photopolymerization method. Jansu water-based microgel can be mass-produced, which is easy to realize industrialization, and the oil phase in the preparation process can be separated and reused. (3) The Jansu microgel prepared by this method has two independent microchambers, in which substances can be loaded to realize its functionalization. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a flow chart of the preparation of Janus water-based microgels prepared in Examples 1-8;

[0029] Figure 2 is a microscope image of the Janus water-based microgel prepared in Example 1;

[0030] Figure 3 is a SEM image of the Janus water-based microgel prepared in Example 1;

[0031] Figure 4 This is a rheological property test diagram of the Janus water-based microgel prepared in Example 1;

[0032] Figure 5 is the infrared spectrum of the Janus water-based microgel prepared in Example 1;

[0033] Figure 6 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 2;

[0034] Figure 7is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 3;

[0035] Figure 8 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 4;

[0036] Fig. 9 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 5;

[0037] Fig.10 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 6;

[0038] Fig.11 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 7;

[0039] Fig.12 is a microscope image of the Janus emulsion and Janus water-based microgel prepared in Example 8;

[0040] Fig.13 is a particle size analysis diagram of the Janus water-based microgels prepared in Examples 1 to 3;

[0041] Fig.14 It is a test diagram of the friction performance of the separated double aqueous phase microgel; (where a is a photo of Janus microgel dissolved in water; b is the friction performance test of pure water, PEG microgel aqueous solution, DEX microgel aqueous solution, and Janus microgel aqueous solution; c is the average friction coefficient of pure water, PEG microgel aqueous solution, DEX microgel aqueous solution, and Janus microgel aqueous solution; b and c are the test results at a load of 10N, a time of 20min, a stroke of 1mm, and a frequency of 1Hz;);

[0042] Fig.15 This is a microscope image of the Janus water-based microgel prepared in Example 4. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific examples and with reference to data. It should be understood that these examples are only for illustrating the present invention and are not intended to limit the scope of the present invention in any way.

[0044] In the following examples, various processes and methods not described in detail are conventional methods well known in the art.

[0045] Example 1

[0046] Dextran (DEX 1000) and PEG8000 were added to deionized water, dissolved and centrifuged to form a two-phase aqueous solution (ATPS), and acrylamide, N, N'-methylenebisacrylamide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were added and stirred to obtain an ATPS aqueous solution with monomers added. The final solution contained 15wt% acrylamide, 2wt% N, N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX10000. 1% Span 80 surfactant was added to liquid paraffin, and the mass ratio of the two-phase aqueous solution with monomers added to the Span80 liquid paraffin solution was 1:4. The weighed biphasic solution was placed in a separatory funnel and allowed to stand for 1 hour. The piston was then opened to remove the lower solution. A small amount of the upper solution was then drained to ensure that no lower solution remained. The entire upper solution was poured out from above. The volume ratio of PEG:DEX in the prepared biphasic solution was 7:3, and the total mass was 5 g. In a 10 mL centrifuge tube, the vortex speed was 3000 rpm and the vortex time was 3 min.

[0047] The obtained Janus inverse emulsion was irradiated under a 300 W ultraviolet lamp for 1 h to initiate acrylamide polymerization to form a three-dimensional network.

[0048] The polymerized solution was washed five times alternately with petroleum ether and ethanol solution and vacuum dried at 25°C to obtain Janus water-based microgel.

[0049] verify: Figure 2 This is a microscope photo of the prepared Janus water-based microgel. Figure 3 This is the SEM image of the invented Janus water-based microgel. Figure 4 For the rheological test of the emulsion before and after illumination, Figure 5 This is the infrared spectrum of Jansu water-based microgel after vacuum drying.

[0050] from Figure 2 Figure 3 Visible: The microscopic morphology of the invented and prepared Janus microgel.

[0051] from Figure 4 It can be seen that after illumination, a linear viscoelastic region formed by the gel clearly appeared.

[0052] from Figure 5 Visible: 3190cm -1 To associate with -NH 2 The characteristic absorption peak is 2926cm -1 The absorption peak of methylene antisymmetric stretching vibration is 2856 cm -1It is the characteristic absorption peak of the symmetric stretching vibration of methylene, 1667cm -1 is the characteristic absorption peak of carbonyl, 1451cm -1 It is the characteristic absorption peak of methylene deformation, indicating that acrylamide is polymerized during the reaction.

[0053] Example 2

[0054] 1. Dissolve 15wt% acrylamide, 2wt% N,N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution. Add 1% Span 80 surfactant to liquid paraffin. Weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 1 hour. Then open the piston, take out the lower solution, and then drain a small part of the upper solution to ensure that there is no lower solution left. Pour all the upper solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 7:3, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 10000rpm and the vortex time is 3min.

[0055] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0056] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0057] 4. Verification: Figure 6 Microscope photograph of the prepared Janus water-based microgel.

[0058] Example 3

[0059] 1. Dissolve 15wt% acrylamide, 2wt% N,N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution. Add 1% Span 80 surfactant to liquid paraffin. Weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 1 hour. Then open the piston, take out the lower solution, and then drain a small part of the upper solution to ensure that there is no lower solution left. Pour all the upper solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 7:3, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 20000rpm and the vortex time is 3min.

[0060] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0061] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0062] 4. Verification: Figure 7 The Janus emulsion and Janus water-based microgel prepared in Examples 1-3 were analyzed for particle size. The results are as follows: Fig.13 shown.

[0063] Example 4

[0064] 15wt% acrylamide, 2wt% N,N′-methylenebisacrylamide, 1wt% 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, 10wt% Na 2 SO 4 Dissolve in deionized water to form a two-phase solution, add 1% Span 80 surfactant to liquid paraffin, and weigh the two-phase solution to Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase solution in a separatory funnel and let it stand for 1 hour, then open the piston, take out the lower solution, and then drain a small part of the upper solution to ensure that there is no lower solution left, and pour all the upper solution from above. The volume ratio of PEG:DEX in the prepared two-phase solution is 7:3, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 3000rpm and the vortex time is 3min.

[0065] verify: Fig.15Microscope photograph of the prepared Janus water-based microgel.

[0066] Example 5

[0067] 1. Dissolve 15wt% acrylamide, 2wt% N,N′-methylenebisacrylamide, 1wt% 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution. Add 1% Span 80 surfactant to liquid paraffin. Weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 2 hours. Then open the piston, take out the lower solution, and then drain a small part of the upper solution to ensure that there is no lower solution left. Pour all the upper solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 4:1, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 3000rpm and the vortex time is 3min.

[0068] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0069] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0070] 4. Verification: Figure 8 Microscope photograph of the prepared Janus water-based microgel.

[0071] Example 6

[0072] 1. Dissolve 15wt% acrylamide, 2wt% N,N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution. Add 1% Span 80 surfactant to liquid paraffin. Weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 4 hours. Then open the piston, take out the lower layer solution, and then drain a small part of the upper layer solution to ensure that there is no lower layer solution left. Pour all the upper layer solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 1:1, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 3000rpm and the vortex time is 3min.

[0073] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0074] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0075] 4. Verification: Fig. 9 Microscope photograph of the prepared Janus water-based microgel.

[0076] Example 7

[0077] 1. Dissolve 15wt% acrylamide, 2wt% N,N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution. Add 1% Span 80 surfactant to liquid paraffin, and weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:1. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 8 hours. Then open the piston, take out the lower layer solution, and then drain a small part of the upper layer solution to ensure that there is no lower layer solution left. Pour all the upper layer solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 1:4, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 3000rpm and the vortex time is 3min.

[0078] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0079] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0080] 4. Verification: Fig.10 Microscope photograph of the prepared Janus water-based microgel.

[0081] Example 8

[0082] 1. Dissolve 15wt% polyethylene glycol diacrylate, 2wt% N,N'-methylenebisacrylamide, 1wt% 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 10wt% PEG 8000, and 10wt% DEX 10000 in deionized water to form a two-phase aqueous solution, add 1% Span 80 surfactant to liquid paraffin, and weigh the two-phase aqueous solution and Span 80 liquid paraffin solution in a mass ratio of 1:4. Place the weighed two-phase aqueous solution in a separatory funnel and let it stand for 4 hours, then open the piston, take out the lower solution to ensure that there is no lower solution left, then drain a small part of the upper solution, and pour all the upper solution from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution is 1:1, and the total mass is 5g. In a 10mL centrifuge tube, the vortex speed is 3000rpm and the vortex time is 3min.

[0083] 2. The obtained Janus inverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate the polymerization of polyethylene glycol diacrylate to form a three-dimensional network.

[0084] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0085] 4. Verification: Fig.11 Microscope photograph of the prepared Janus water-based microgel.

[0086] Example 9

[0087] 1. 15wt% acrylamide, 2wt% N,N′-methylenebisacrylamide, 1wt% 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 1wt% TiO 2 , 10wt% PEG 8000, 10wt% DEX 10000 were dissolved in deionized water to form a two-phase aqueous solution, 1% Span 80 surfactant was added to liquid paraffin, and the mass ratio of the two-phase aqueous solution to the Span 80 liquid paraffin solution was weighed to be 1:4. The weighed two-phase aqueous solution was placed in a separatory funnel and allowed to stand for 4 hours, then the piston was opened, the lower layer solution was taken out to ensure that no lower layer solution remained, and then a small amount of the upper layer solution was released, and all the upper layer solution was poured out from above. The volume ratio of PEG:DEX in the prepared two-phase aqueous solution was 1:1, and the total mass was 5g. In a 10mL centrifuge tube, the vortex speed was 3000rpm and the vortex time was 3min.

[0088] 2. The obtained Janus reverse emulsion was irradiated under a 300W ultraviolet lamp for 1 hour to initiate acrylamide polymerization to form a three-dimensional network.

[0089] 3. The polymerized solution was washed five times alternately with petroleum ether and ethanol solution, and vacuum dried at 25°C to obtain Janus water-based microgel.

[0090] 4. Verification: Fig.12 Microscope photograph of the prepared Janus water-based microgel.

[0091] Example 10

[0092] Friction test performance of Janus microgel aqueous solution under constant load

[0093] The Janus microgel prepared in Example 1 was tested by a friction and wear testing machine with a particle content of 10 wt %, a friction pair of a 304 stainless steel ball with a diameter of 4.5 mm and a 304 stainless steel plate with a size of 30×12 mm, a constant load of 10 N, a sliding frequency of 1 Hz, an amplitude of 1 mm, and a test time of 20 min.

[0094] Verification: If Fig.14 a shows the dispersion of Janus microgel particles in water; Fig.14 bc is the test result of the friction coefficient between the friction pairs under the conditions of a load of 10N, a sliding frequency of 1Hz, and an amplitude of 1mm. The results show that the Janus microgel prepared by the present invention has a good anti-friction effect.

Claims

1. A method for preparing a Janus water-based microgel, characterized in that: The following steps are involved: (1) Construction of a biphasic aqueous phase containing polymerized monomers: sodium sulfate and polyethylene glycol or dextran and polyethylene glycol are added to deionized water, dissolved and centrifuged to form a biphasic aqueous ATPS solution; polymerized monomers, crosslinking agents and initiators are added to ATPS, stirred, dissolved and centrifuged to obtain a monomer-added ATPS aqueous solution; (2) Preparation of Janus emulsion and Janus microgel: prepare an oil solution containing a surfactant, add the ATPS aqueous solution containing the monomer to the oil solution containing the surfactant, use a vortex shaker to shake into an emulsion, place the emulsion in a light irradiation reaction chamber, and use ultraviolet light to irradiate and stir to obtain Janus microgel; (3) Drying of Janus microgel: The Janus microgel obtained after light irradiation is washed and dried to obtain the Janus microgel.

2. The preparation method according to claim 1, characterized in that: In step (1), the polymerization monomer is acrylamide, polyethylene glycol diacrylate or N-isopropyl acrylamide; the crosslinking agent is N,N′-methylenebisacrylamide; and the initiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone.

3. The preparation method according to claim 1, characterized in that: In step (2), the surfactant is Span 80; the oil phase is liquid paraffin and sunflower oil; the emulsification speed of the emulsification using a vortex shaker is 2000-20000 rpm, and the emulsification time is 1-5 min.

4. The method according to claim 1, characterized in that: If a rotor is used as an agitator in step (1), the rotation speed is 500 to 1000 rpm.

5. The preparation method according to claim 1, characterized in that: The wavelength of the ultraviolet lamp in step (3) is 300-400nm.

6. The preparation method according to claim 1, characterized in that: The washing in step (3) is performed by alternately washing with ethanol and petroleum ether and drying to obtain the Janus water-based microgel.

7. The preparation method according to claim 1, characterized in that: In step (1), the mass concentration of the polymerized monomer is 5% to 30%, the mass fraction of the initiator to the monomer is 0.1% to 3%, and the mass concentration of the crosslinking agent to the monomer is 1% to 20%.

8. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of oil to water is 10 / 1 to 2 / 1, and the concentration of surfactant Span 80 in the oil is 1% to 5%.

9. The preparation method according to claim 1, characterized in that: The polyethylene glycol described in step (1) is PEG 8000, with a mass concentration of 10% to 25%; the dextran is DEX 10000, with a mass concentration of 10% to 25%; and the mass concentration of sodium sulfate is 10% to 25%.

10. The preparation method according to claim 1, characterized in that: The molecular weight of PEG is selected from 2000 to 25000, and the molecular weight of DEX is selected from 2000 to 25000.

Citation Information

Patent Citations

  • Method for synthesizing high molecular double-sided particles in batches by taking double-sided emulsion as template

    CN103788267A

  • Microgel based on acryloylated gelatin as well as preparation method and application of microgel

    CN115418006A

  • Method for preparing asymmetric polymer microsphere in UV light field

    CN101423568A

  • Method for preparing Janus particles and morphology regulation and control method

    CN113457566A

  • Porous anisotropic polymer microsphere and preparation method thereof

    CN113999335A